(3EOGQI GdehGQO GdHTQjI (B/s - (3QHGHYI, Ydjs ((3YeGf(B: s (3OGQ UaGA ddfTQ(B, s, 2003)
(3eaghe GOGQI GdehGQO GdHTQjI, JMdjd GdCYeGd, MOjO GdGMJjGLGJ GdHTQjI ddefXeI, JMOjO GdGMJjGLGJ GdJOQjHjI, fXe GdCLhQ hGdQhGJH, Jbjje BOGA GdYGedjf, GdJShjb, GdeRjL GdJShjbj(B.s
(3GdeQGLY U(B.167s
Keywords: (3EOGQI GdCaQGOs; (3GdJShjbs; (3GdehGQO GdHTQjIs